Anesthetic Considerations in Hepatectomies under Hepatic Vascular Control. (28th May 2012) - Tympa, Aliki; Theodoraki, Kassiani; Tsaroucha, Athanassia; Arkadopoulos, Nikolaos; Vassiliou, Ioannis; Smyrniotis, Vassilios
Abstract : Background . Hazards of liver surgery have been attenuated by the evolution in methods of hepatic vascular control and the anesthetic management. In this paper, the anesthetic considerations during hepatic vascular occlusion techniques were reviewed. Methods . A Medline literature search using the terms "anesthetic, " "anesthesia, " "liver, " "hepatectomy, " "inflow, " "outflow occlusion, " "Pringle, " "hemodynamic, " "air embolism, " "blood loss, " "transfusion, " "ischemia-reperfusion, " "preconditioning, " was performed. Results . Task-orientated anesthetic management, according to the performed method of hepatic vascular occlusion, ameliorates the surgical outcome and improves the morbidity and mortality rates, following liver surgery. Conclusions . Hepatic vascular occlusion techniques share common anesthetic considerations in terms of preoperative assessment, monitoring, induction, and maintenance of anesthesia. On the other hand, the hemodynamic management, the prevention of vascular air embolism, blood transfusion, and liver injury are plausible when the anesthetic plan is scheduled according to the method of hepatic vascular occlusion performed.